Эколого-геохимическая оценка территории г. Юрга по данным изучения снегового покрова (Кемеровская область); Инженерная экология - 2021 - Будаева Ю. С. Юлия Сергеевна; Таловская А. В. Анна Валерьевна; Язиков Е. Г. Егор Григорьевич; Торосян Е. С. Елена Самвеловна (2021, 2021)
Заглавие с экрана